Perubahan Bunyi Pada Kata Serapan Dalam Teks Terjemahan Mamo Zein Karya Abdun Said Ibnu Abdullah - Maharani, Sabrina; Abdullah, Abdullah; Darsita, Darsita; Satori, Achmad; Mahmud, Faisal (UIN ANTASARI, 2024)
Arabic language has a considerable influence on Indonesian language in terms of vocabulary or word absorption. This study aims to identify various forms of sound changes that occur in the novel Mamo-Zein by Ramadhan el-Bauthy. This study uses qualitative descriptive analysis, researchers examine the data to distinguish Arabic loanwords in the text that use Indonesian phonemes. The result of the study found 33 loanwords in the novel Mamo-Zein. The researcher used Crowley's theory of sound change and found several phonological variations in the form of weakening and adding sounds. This research is expected to add knowledge in the field of linguistics and help readers in choosing and distinguishing standardised absorption words in Indonesian.